Improved Estimators of the Mean of a Normal Distribution with a Known Coefficient of Variation - Wuttichai Srisodaphol; Noppakun Tongmol (Journal of Probability and Statistics)
This paper is to find the estimators of the mean θ for a normal distribution with mean θ and variance aθ2, a>0, θ>0. These estimators are proposed when the coefficient of variation is known. A mean square error (MSE) is a criterion to evaluate the estimators. The results show that the proposed estimators have preference for asymptotic comparisons. Moreover, the estimator based on jackknife technique has preference over others proposed estimators with some simulations studies.